Prospects of antigen-specific therapy in type 1 diabetes mellitus - Tatiana Vasil'evna Nikonova; Yulia Viktorovna Alekseeva (Сахарный диабет)
Type 1 diabetes mellitus is commonly recognized as an autoimmune disease characterized by progressive destruction of pancreatic ?-beta-cells. Progress in diagnostics at preclinical stage is accompanied with active development of preventive measures. So far, there are no specific therapeutic agents approved for clinical practice. However, ongoing large-scale studies have outlined some promising solutions, antigen-specific immunotherapy being one of them.